Pancreatite aguda biliar na infância - Menin,Flavio Augusto (2006)
Acute pancreatitis is an uncommon condition in childhood. Gallstones rarely cause pancreatitis in children. Instead, the leading causes of pancreatitis tend to be trauma, infecctions, drugs, congenital disorders. One rare case of acute gallstone pancreatitis in children is described, showing the diagnosis clinical/radiologic and surgery treatment (videocolecistectomy).